2019
DOI: 10.1101/738260
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Penetrance of Parkinson’s disease in LRRK2 p.G2019S carriers is modified by a polygenic risk score

Abstract: Phone Number: 301-435-7606 Fax Number: 301-451-7295 Word count Running title PRS for penetrance of PD with LRRK2 p.G2019S AbstractBackground: While the LRRK2 p.G2019S mutation has been demonstrated to be a strong risk factor for Parkinson's Disease (PD), factors that contribute to penetrance among carriers, other than aging, have not been well identified.Objectives: To evaluate whether a cumulative genetic risk identified in the recent genome-wide study is associated with penetrance of PD among p.G2019S mutati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 23 publications
1
31
0
Order By: Relevance
“…there are many genetic variants each with a small effect that collectively have a significant effect on the risk of PD in LRRK2 mutation carriers. This result is in line with the recent analysis of Iwaki et al 57 In that study, a PRS was derived using 89 genome-wide significant variants (some of which were also included in our PRS) identified in a PD GWAS of Nalls et al 4 . Iwaki et al found that the PRS was significantly associated with the penetrance of the LRRK2 G2019S mutation.…”
Section: Discussionsupporting
confidence: 88%
“…there are many genetic variants each with a small effect that collectively have a significant effect on the risk of PD in LRRK2 mutation carriers. This result is in line with the recent analysis of Iwaki et al 57 In that study, a PRS was derived using 89 genome-wide significant variants (some of which were also included in our PRS) identified in a PD GWAS of Nalls et al 4 . Iwaki et al found that the PRS was significantly associated with the penetrance of the LRRK2 G2019S mutation.…”
Section: Discussionsupporting
confidence: 88%
“…Because AAO genetic modifiers have been nominated for LRRK2 + /PD + , effect sizes have been small and ethnicity/populations seem to play a role. 11,[15][16][17][18] This study establishes a connection between environmental and lifestyle factors that adds to the complexity in LRRK2 + /PD + .…”
Section: Discussionmentioning
confidence: 59%
“…All GWAS loci and summary statistics were gathered from our recent PD GWAS studies. [2][3][4][5]14,15 We selected all genes 1 megabase (Mb) up and downstream of each significant variant from the hg19 reference genome. 16 Genes in this 2-Mb range were included in locus zoom plots created for each variant.…”
Section: Gwas Loci and Gene Selectionmentioning
confidence: 99%